Pemodelan Kapabilitas UMKM Dalam Perdagangan Hijau Berkelas Dunia : Studi Kasus UMKM Provinsi DI Yogyakarta - Alfarizi, Muhammad; Sari, Rini Kurnia (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2024)
Global warming and climate change demand sustainable responses from the business sector, including SMEs, which are now the largest contributors to emissions. SMEs in Indonesia, especially in the DI Yogyakarta Province, have the potential to become key players in world-class green trade. This study aims to investigate the influence of transportation infrastructure, logistics capabilities, and Green Information System on the capabilities of SMEs in the DI Yogyakarta Province in world-class green trade. The study adopts a quantitative approach based on a survey of 225 SME owners in the DI Yogyakarta Province. Purposive sampling technique was selected and analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results show that transportation infrastructure substantially influences the ability of SMEs' green supply chains and global logistics. The logistics capabilities of SMEs in Yogyakarta have a positive impact on the capabilities of green supply chains. The implementation of GIS has also been shown to enhance the capabilities of green supply chains and international logistics by providing visibility, transparency, and efficiency in business operations. The influence of supply chain capabilities was found to be significantly positive on international logistics. The research findings affirm the crucial role of green supply chain capabilities and international logistics in enhancing the capabilities of SMEs to enter international trade.